Notch signalling patterns retinal composition by regulating atoh7 during post-embryonic growth - Pérez Saturnino, Alicia; Lust, Katharina; Wittbrodt, Joachim (Development, 2018)
Skip to Next Section - Patterning of a continuously growing naive field in the context of a life-long growing organ such as the teleost eye is of high functional relevance. Intrinsic and extrinsic signals have been proposed to regulate lineage specification in progenitors that exit the stem cell niche in the ciliary marginal zone (CMZ). The proper cell-type composition arising from those progenitors is a prerequisite for retinal function. Our findings in the teleost medaka (Oryzias latipes) uncover that the Notch-Atoh7 axis continuously patterns the CMZ. The complement of cell types originating from the two juxtaposed progenitors marked by Notch or Atoh7 activity contains all constituents of a retinal column. Modulation of Notch signalling specifically in Atoh7-expressing cells demonstrates the crucial role of this axis in generating the correct cell-type proportions. After transiently blocking Notch signalling, retinal patterning and differentiation is re-initiated de novo. Taken together, our data show that Notch activity in the CMZ continuously structures the growing retina by juxtaposing Notch and Atoh7 progenitors that give rise to distinct complementary lineages, revealing coupling of de novo patterning and cell-type specification in the respective lineages.